2011
DOI: 10.4103/1463-1741.82958
|View full text |Cite
|
Sign up to set email alerts
|

Using the Extended Parallel Process Model to create and evaluate the effectiveness of brochures to reduce the risk for noise-induced hearing loss in college students

Abstract: Brochures containing messages developed according to the Extended Parallel Process Model were deployed to increase intentions to use hearing protection for college students. These brochures were presented to one-half of a college student sample, after which a questionnaire was administered to assess perceptions of threat, efficacy, and behavioral intentions. The other half of the sample completed the questionnaire and then received brochures. Results indicated that people receiving the brochure before the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…More specifically, research suggests that there are cultural differences in the perceptions of music exposure, and that these perceptions may be linked to attitudes toward hearing loss and its related consequences (for a review, see Zhao et al, 2012). On a different note, knowledge of risk does not necessarily result in healthy listening behavior at the individual level (Kotowski et al, 2011). Hence, health promotion strategies should focus on changing not merely individual attitudes, but also societal norms and regulations to decrease noise-induced auditory symptoms among adolescents (Landälv et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, research suggests that there are cultural differences in the perceptions of music exposure, and that these perceptions may be linked to attitudes toward hearing loss and its related consequences (for a review, see Zhao et al, 2012). On a different note, knowledge of risk does not necessarily result in healthy listening behavior at the individual level (Kotowski et al, 2011). Hence, health promotion strategies should focus on changing not merely individual attitudes, but also societal norms and regulations to decrease noise-induced auditory symptoms among adolescents (Landälv et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that knowledge about risk of hearing loss as a result of loud noise or music does not lead to healthy listening behavior (for a review, see Zhao et al, 2012). For example, Kotowski et al (2011) evaluated the effectiveness of education provided through brochures to reduce the risk of noise-induced hearing loss in college students. Their study results indicated that although people's receiving the brochure resulted in a greater perception of hearing loss and the efficacy of using earplugs when in loud environments, intentions to use earplugs were unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…[52] indicated that perceived response efficacy and perceived threat were significantly correlated to drinking alcohol. Other studies[5354] reported that perceived response efficacy and their effect on change in behavior increased after educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, when both the perceived threat and efficacy were high, individuals were more likely to activate the danger control process, which led them to adaptive responses (accept the recommended response). In this process, individuals were motivated to control the danger because they were motivated to enact protection behaviors, and their attitudes and behavioral intentions changed in accordance with the message recommendations in order to prevent the negative outcomes induced by the threat [18,19]. When the perceived threat was high and the perceived efficacy is low, individuals were more likely to activate the fear control process by engaging in maladaptive responses (message rejection).…”
Section: The Role Of Fear In the Eppmmentioning
confidence: 99%
“…The EPPM included both message components and cognitive processes related to fear appeals, and it was proposed based on the perspective that fear control was more cognitive than emotional [13,16]. The EPPM has been used to investigate in a variety of health topics including cardiovascular disease prevention [18], reducing noise-induced hearing loss [19], colonoscopy screening promotion [20], skin cancer prevention [21], general TV health news processing [22], and promoting breast cancer screening [9]. Although the EPPM is an effective theoretical framework in fear appeal studies, there are still gaps to be filled in the model.…”
mentioning
confidence: 99%